Property rights and land use change: Implications for sustainable resource management in Borana, southern Ethiopia - Kamara, A.; Kirk, M.; Swallow, B.M. (Informa UK Limited, 2005)
The Borana rangelands occur in a semi-arid area in southern Ethiopia, characterized by extensive livestock production. The area is a valuable source of livestock that generates income and livelihoods for large numbers of rural dwellers, and export earnings for Ethiopia's fragile economy. Despite the region's high ecological potential vis-a-vis livestock production, the area is still in a crisis today with limited success of development interventions, due to increasing pressure on the appropriation of land by private individuals, with aggravated impacts of droughts, emerging conflicts and destitution. These trends are hypothetically attributed to various factors, including climatic, demographic and market forces. The paper utilizes data from 40 pastoral communities in the area to identify the causes of these trends and the potential consequences on rural livelihoods. The study infers that the Borana pastoral system is in transition, with evidence of departure from traditional pastoralism to a semi-sedentary system with increasing reliance on crops and private grazing. The semi-arid nature of the area (aggregate mean rainfall between 300 mm and 900 mm per annum) creates a concern about the capacity of the area to support a fully privatized system on a sustainable basis.